Enterocin Ent7420 – a potential postbiotic additive: effect on growth, immune response and gut health in MRSE-infected rabbits - Pogány Simonová, Monika; Chrastinová, Ľubica; Ščerbová, Jana; Tokarčíková, Katarína; Grešáková, Ľubomíra; Žitňan, Rudolf; Plachá, Iveta; Lauková, Andrea (Frontiers in Veterinary Science, 2025)
Increasing occurrence of methicillin-resistant (MR) staphylococci in humans and animals leads to special attention because of their difficult treatment and zoonotic character. Therefore, novel natural antimicrobial compounds directed against antibiotic-resistant bacteria are requested to overcome this problem. Currently, bacteriocins/enterocins (proteinaceous substances with antimicrobial activity produced by several lactic acid bacteria/enterococci) present a new promising strategy, both in prevention and treatment. The aim of this work was to evaluate the effect of Enterocin Ent7420 against the MR Staphylococcus epidermidis SEP3/Tr2a (MRSE) strain in a rabbit (food animal) model, testing its influence and protective effect on body weight (BW), feed conversion ratio (FCR), phagocytic activity (PA), serum glutathione-peroxidase (GPx) enzyme activity, and jejunal morphology (JM). Ninety-six weaned broiler rabbits were divided into experimental groups S (MRSE strain; to simulate the pathogen attack), E (Ent7420), E + S (Ent7420 + MRSE), and control group (C; without substances). Higher BW and lower FCR (NS) were recorded during Ent7420 application. Decreased JM values (p < 0.05) reflect the MRSE strain’s damaging effect on the rabbit organism. Improved parameters of GPx and JM during substance combination suggest that Ent7420 may mitigate staphylococcal pathogenesis, warranting further investigation. These results suggest not only promising preventive use of Ent7420 to improve the growth and immunity of rabbits but also its protective effect against possible staphylococcal (MRSE) infections in rabbit breeding.